EMPREGO DO DUP NA DESINFECÇÃO DE CRIAÇÕES DO BICHO-DA-SEDA - Campos, Antonio Rodrigues; Abreu, Oldemar Cardim; Oliveira, Domingos Azevedo (REVISTA DE AGRICULTURA, 2020)
EMPREGO DO DUP NA DESINFECÇÃO DE CRIAÇÕES DO BICHO-DA-SEDA